Private and data property - Risse, Verena (IE University, 2020)
This contribution explores questions related to the protection and governance of private data by drawing on the analogy between privacy and property. Although this analogy is not entirely new, property and the defense of property rights remain one of the most common ways in which rights to private data are discussed in both legal and philosophical debates. Accordingly, the paper starts out by presenting theories of property generation and acquisition and adapts these to the generation and collection of private data. Similarly to property, data as such does not independently exist; it is something created by human beings. Data exists because it is measured, gathered and organized. When it comes to the acquisition of personal data, however, one cannot assume—as in the case of property—that the person who gathers data automatically owns it. Thus, it seems important to note that—unlike the case of property—generation and acquisition of data do not automatically go hand in hand. Yet, once data exists, questions of how it is protected, acquired and transmitted remain and property rights provide a helpful starting point in searching for answers.
Keywords: Protection and governance of private data; Protección y gobernanza de datos privados.; Ptivacy; Privacidad; Property; Propiedad; Personal Data; Datos personales; Marketing; Technology; Tecnología; General Data Protection Regulation; GDPR; Regulación General de Protección de Datos; RGPD